The Effect Of Interest Rates And Exchange Rates On Stock Prices In Cigarette Manufacturing Companies Listed On The IDX - Mursidah Abu; Bustam Bustam; Patta Rapanna (Utan Kayu Publishing, 2024)
The capital market is a means for investors to bring together sellers and buyers of funds to invest in stocks. The official institution that handles the sale and purchase of shares is the Indonesia Stock Exchange (IDX). One of the companies that are attractive to investors is manufacturing companies because manufacturing companies are an industry that dominates companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach while based on the level of explanatory, this research is classified as associative research. Associative research is research that aims to determine the influence or causal relationship, namely the independent variable (X) to the bound or dependent variable (Y). This research was conducted on cigarette sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX). From the results of testing and analyzing the effect of interest rates on stock prices in cigarette manufacturing companies sub-sector is not very significant to companies listed on the IDX and from the results of testing and analyzing exchange rates on stock prices in manufacturing companies in the cigarette sub-sector has a significant influence on companies listed on the IDX.